Respuesta :
Which expression is equivalent to x + y + x + y + 3(y + 5)? 2x + 5y + 5 2x + y + 30 2x + 5y + 15 2x + 3y + 10
[tex] x + y + x + y + 3(y + 5)= \\ \\ x+y+x+y+3y+15= \boxed{ 2x+5y+15 } [/tex]
[tex] x + y + x + y + 3(y + 5)= \\ \\ x+y+x+y+3y+15= \boxed{ 2x+5y+15 } [/tex]
Answer:
Option 3 - [tex]x+y+x+y+3(y + 5)=2x+5y+15[/tex]
Step-by-step explanation:
Given : Expression [tex]x + y + x + y + 3(y + 5)[/tex]
To find : Which expression is equivalent to given expression ?
Solution :
Expression [tex]x + y + x + y + 3(y + 5)[/tex]
Open the bracket,
[tex]x + y + x + y + 3y +15[/tex]
Add like terms,
[tex]2x+5y+15[/tex]
Therefore, [tex]x + y + x + y + 3(y + 5)=2x+5y+15[/tex]
So, option 3 is correct.